Dados o polinômios A = 3x(elevado a 2) + 6x + 2xy, B = - 2x(elevado a 2) - 4xy e C = 2x, calcule:
a) 2A + B
b)B:C
Soluções para a tarefa
Respondido por
2
A =
![3 {x}^{2} + 6x + 2xy 3 {x}^{2} + 6x + 2xy](https://tex.z-dn.net/?f=3+%7Bx%7D%5E%7B2%7D++%2B+6x+%2B+2xy)
B =
![- 2 {x}^{2} - 4xy - 2 {x}^{2} - 4xy](https://tex.z-dn.net/?f=+-+2+%7Bx%7D%5E%7B2%7D++-+4xy)
C =
![2x 2x](https://tex.z-dn.net/?f=2x)
a)
![2a \: + b 2a \: + b](https://tex.z-dn.net/?f=2a+%5C%3A++%2B+b)
![2( \: 3 { {x}^{2} + 6x + 2xy}) - 2 {x}^{2} - 4xy 2( \: 3 { {x}^{2} + 6x + 2xy}) - 2 {x}^{2} - 4xy](https://tex.z-dn.net/?f=2%28+%5C%3A+3+%7B+%7Bx%7D%5E%7B2%7D++%2B+6x+%2B+2xy%7D%29++-+2+%7Bx%7D%5E%7B2%7D++-+4xy)
![6 {x}^{2} + 12x + 4xy - 2 {x}^{2} - 4xy 6 {x}^{2} + 12x + 4xy - 2 {x}^{2} - 4xy](https://tex.z-dn.net/?f=6+%7Bx%7D%5E%7B2%7D++%2B+12x+%2B+4xy+-+2+%7Bx%7D%5E%7B2%7D+-+4xy+)
![6 {x}^{2} - 2 {x}^{2} + 4xy - 4xy + 12x 6 {x}^{2} - 2 {x}^{2} + 4xy - 4xy + 12x](https://tex.z-dn.net/?f=6+%7Bx%7D%5E%7B2%7D++-+2+%7Bx%7D%5E%7B2%7D++%2B+4xy+-+4xy+%2B+12x)
![4 {x}^{2} + 12x 4 {x}^{2} + 12x](https://tex.z-dn.net/?f=4+%7Bx%7D%5E%7B2%7D++%2B+12x)
b)
![\frac{ - 2 {x}^{2} - 4xy }{2x} \frac{ - 2 {x}^{2} - 4xy }{2x}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+2+%7Bx%7D%5E%7B2%7D+-+4xy+%7D%7B2x%7D+)
![- {x} - 2y - {x} - 2y](https://tex.z-dn.net/?f=+-++%7Bx%7D++-+2y)
B =
C =
a)
b)
Respondido por
0
.........................................................
Perguntas interessantes